2010
DOI: 10.1016/j.bbamcr.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

ErbB4 regulates the timely progression of late fetal lung development

Abstract: The ErbB4 receptor has an important function in fetal lung maturation. Deletion of ErbB4 leads to alveolar hypoplasia and hyperreactive airways similar to the changes in bronchopulmonary dysplasia (BPD). BPD is a chronic pulmonary disorder affecting premature infants as a consequence of lung immaturity, lung damage, and abnormal repair. We hypothesized that proper ErbB4 function is needed for the timely progression of fetal lung development. An ErbB4 transgenic cardiac rescue mouse model was used to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 37 publications
(56 reference statements)
2
46
0
Order By: Relevance
“…This delay is most prominent at the transition from the canalicular to the saccular stage on Embryonic Day 17. Delayed saccular development, with an increased mesenchymal area around the airspaces and a delayed onset of surfactant synthesis and Sftpb expression in HER4 heart (2/2) lungs, confirms the important role of the ErbB4 receptor in the regulation of the timely progression of fetal lung development (5). We here expand on the exact ErbB4 signals that regulate the expression of Sftpb in the isolated fetal Type II epithelial cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This delay is most prominent at the transition from the canalicular to the saccular stage on Embryonic Day 17. Delayed saccular development, with an increased mesenchymal area around the airspaces and a delayed onset of surfactant synthesis and Sftpb expression in HER4 heart (2/2) lungs, confirms the important role of the ErbB4 receptor in the regulation of the timely progression of fetal lung development (5). We here expand on the exact ErbB4 signals that regulate the expression of Sftpb in the isolated fetal Type II epithelial cell.…”
mentioning
confidence: 99%
“…In the fetal lung, NRG is required for the initiation of fetal surfactant synthesis (4), and ErbB receptors (named because of their homology to the erythroblastoma viral gene product, v-erbB), also known as human epidermal growth factor receptors (HERs), are involved in the timely progression of fetal lung cell differentiation (4)(5)(6).…”
mentioning
confidence: 99%
“…We have previously shown that pulmonary ErbB4 deletion leads to a lung phenotype in fetal and adult animals, including a delayed onset of fetal surfactant synthesis and Sftpb expression (Liu 2010), accompanied by decreased alveolar space and increased thickness of alveolar septae, mirroring the pathologic picture of bronchopulmonary dysplasia. However, these lungs exhibit catch-up expression on the effects of ErbB4 deletion at term, resulting in normal Sftpb gene expression in adult animals (Purevdorj 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ErbB receptors are important regulators of cell proliferation, maturation and differentiation (Gassmann 1995). In the fetal lung, ErbB4 protein is highly expressed in fetal alveolar type II (ATII) cells (Liu 2007) and is necessary for the timely initiation of surfactant expression and synthesis (Dammann 2003) and the progression of morphologic lung development (Liu 2010). ErbB4 is unique in the ErbB family of tyrosine kinase receptors, since it can be cleaved by presenillin (Hoeing 2011;Fiaturi 2014), expresses strong nuclear signaling (Williams 2004) and interacts with transcription factors such as Stat5A (Zscheppang 2011) and TTF-1 (Zscheppang 2013) that are important in promoting Sftpb expression in ATII cells.…”
Section: Introductionmentioning
confidence: 99%
“…S1 and S2. 1 development (27) and alveolar simplification (26) and downregulation of ErbB4 receptors in cultured type II cells blocked neuregulin stimulation of surfactant production (24). Therefore, given the role of ErbB4 in epithelial cells maturation, we investigated whether this receptor participates in stretch-induced signaling and type II cell differentiation.…”
mentioning
confidence: 99%